3D printing of highly reinforced composite - Teh, Jeslyn Jia Lin (Nanyang Technological University, 2021)
It has always been a challenge to alter and influence ceramics and composites' microstructure that possess high solid concentration because of its high viscosity. With the advancement in material science and engineering, 3D printing of ceramic composite material has become the subject of very rapidly growing research activities. It opens a new horizon and unlimited possibilities for the manufacturing industry, especially in terms of geometrical flexibility, speed of manufacturing, and sustainability. One of the promising method is the development of suitable 3D ink slurry to fabricate ceramic into complex shapes while retaining its mechanical properties.